Assessment of Oocyte Retrieval and its Quality from the Abattoir Ovaries of Jaffarabadi Buffaloes by Aspiration and Slicing Methods - Parmar, Kiran H.; Raval, Rupesh J.; Vala, Karshan B.; Patbandha, Tapas (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Present study was carried out to assess the efficacy of aspiration and slicing methods of oocytes retrieval, retrieval rate and grades of oocytes recovered from the abattoir ovaries of culled Jaffarabadi buffaloes. The ovaries were procured from local abattoir (n=100), and the oocytes from 50 ovaries each were retrieved by slicing and aspiration method, which yielded 205 and 148 oocytes of different grades, respectively. Among the two methods of oocytes retrieval, the slicing method yielded significantly (P <0.01) higher average number of oocytes (4.12 ± 0.34) than the aspiration method (2.96 ± 0.29). Recovery rate of oocytes was 3.57 and 4.18 by slicing method, and 0.65 and 3.23 in aspiration method in the presence of CL and absence of CL, respectively. The mean numbers of Grade B oocytes retrieved by slicing method in the presence and absence of CL on ovary (2.00 ± 0.44, 2.19 ± 0.23) were significantly higher (p <0.05) than grade A (0.29 ± 0.19, 0.23 ± 0.08), grade C (0.43 ± 0.20, 0.35 ± 0.11) and grade D (0.86 ± 0.14, 1.42 ± 0.19, resp.). Similarly, the mean numbers of Grade B oocytes retrieved by aspiration method in the presence and absence of CL on ovary (0.50 ± 0.34, 1.59 ± 0.23) were higher than grade A (0.33 ± 0.21, 0.27 ± 0.07), grade C (0.17 ± 0.17, 0.25 ± 0.09) and grade D (0.00 ± 0.00, 1.11 ± 0.16, resp.). The better oocytes retrieval and good quality of oocytes were yielded by slicing method as compared to aspiration method in the absence of CL.